Bringing the median voter back in: The relationship between government debt, median voter preferences, and welfare state spending. (May 2014) - Tromborg, Mathias Wessel
Welfare state spending cuts are effective fiscal consolidation tools, but some policymakers use other fiscal policy tools to address high levels of government debt. I argue that the economic incentive to cut welfare spending when government debt is high is undermined by the political incentive to stay in power when the median voter opposes retrenchment. Using survey data to measure the policy position of the median voter as well as hard figures on government debt and government social spending from 18 Organisation for Economic Co-operation and Development (OECD) countries, I estimate a series of regressions that show that government debt has a negative effect on social spending, but only when the median voter does not oppose retrenchment. This holds true for broad measures of social spending as well as for unemployment spending and old-age pension spending.